Pengaruh Pijat Bayi terhadap Kualitas Tidur pada Bayi Umur 3-6 Bulan di BPM Aida Nospita Desa Manunggal Kecamatan Labuhan Deli Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2025 - Nopalina Suyanti Damanik; Nur Azizah; Marlina Tafonao; Riska Hutapea (Pusat Riset dan Inovasi Nasional, 2025)
Sleep disturbances in infants can cause significant physiological and psychological impacts, such as decreased immune function, impaired cognitive development, and an increased risk of emotional problems (Tanty & Pramesti, 2023). Poor sleep not only inhibits physical growth but also affects infants’ mental development, including attention disorders, anxiety, and low cognitive abilities (Hendri & Sari, 2021). Therefore, it is important to provide effective interventions to improve infants’ sleep quality. This study aimed to determine the effect of baby massage on infant sleep quality at BPM Aida Nospita, Manunggal Village, Labuhan Deli Subdistrict, Deli Serdang Regency, North Sumatra Province, in 2025. This research employed a quasi-experimental method with a pretest–posttest design using an experimental group and a control group, also known as a pretest–posttest with control group design, which is a form of quasi-experimental research design. The population of this study consisted of all infants aged 3–6 months at BPM Aida Nospita, Manunggal Village, Labuhan Deli Subdistrict, Deli Serdang Regency, North Sumatra Province, totaling 32 infants, with 16 infants in the experimental group and 16 infants in the control group. The results of the statistical analysis using the Wilcoxon test showed a significant probability value of 0.001 (p < 0.05). This indicates that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted, meaning that baby massage had a significant effect on sleep quality among infants at BPM Aida Nospita, Manunggal Village, Labuhan Deli Subdistrict, Deli Serdang Regency, North Sumatra Province, in 2025.